Application Prospect of Space-Integrated-Ground Information Network in Railway - Kaifeng WANG; Xiangbao KAI; Ming LI; Yuan GAO; Yun LIU; Jinchuan CHAI (天地一体化信息网络)
With the advantages of wide coverage, no geographical restrictions and convenient establishment, the spaceintegrated-ground information network can integrate with the existing railway communication network and expand the railway communication service capacity and service scope.Based on the analysis of the application status of railway communication system in China, the application requirements of the space-integrated-ground information network from the aspects of railway business, technical development and intelligent railway construction were discussed.The overall application framework of the space-integrated-ground information network was put forward, the access mode and application mode of the network and satellite terminals were designed, and the typical application requirements in railway survey and construction, emergency rescue, railway operation and security were analyzed.